Ocular neuromyotonia. Issue 5 (21st February 2018) - Soares-dos-Reis, Ricardo; Martins, Ana Inês; Brás, Ana; Matos, Anabela; Bento, Conceição; Lemos, João
Abstract : Ocular neuromyotonia is a rare, albeit treatable, ocular motor disorder, characterised by recurrent brief episodes of diplopia due to tonic extraocular muscle contraction. Ephaptic transmission in a chronically damaged ocular motor nerve is the possible underlying mechanism. It usually improves with carbamazepine. A 53-year-old woman presented with a 4-month history of recurrent episodes of binocular vertical diplopia (up to 40/day), either spontaneously or after sustained downward gaze. Between episodes she had a mild left fourth nerve palsy. Sustained downward gaze consistently triggered downward left eye tonic deviation, lasting around 1 min. MR scan of the brain was normal. She improved on starting carbamazepine but developed a rash that necessitated stopping the drug. Switching to lacosamide controlled her symptoms.